Results of the Ponseti method after congenital clubfoot recurrence subjected to posteromedial release: A retrospective study of 57 feet - de Alvarenga Borges da Fonsêca, Elizabeth; Paschoal Nogueira, Monica (Journal of the Foot & Ankle, 2026)
Introduction: The treatment of congenital clubfoot (CCF) relied on corrective surgeries, such as posteromedial release, as the method of choice, especially in cases of recurrence. However, such surgeries were associated with stiffness, pain, and recurrence. This study aims to evaluate the efficacy of the Ponseti Method in patients with recurrence after posteromedial release. Methods: Descriptive retrospective study of 40 children (57 feet) with recurrence of CCF previously submitted to posteromedial release, treated with the Ponseti Method between 2001 and 2024. The protocol included serial manipulations with weekly casts until the deformities were corrected. In patients > 4 years of age, in addition to serial casts, tenotomy and transposition of the anterior tibial tendon were performed. The final evaluation was performed using the Pirani score and the functional classification of Nogueira et al. (2017), which classifies the results as “excellent”, “good”, “regular”, and “poor”. Results: The mean age at the first visit was five years and five months (range: 9 months to 16 years). Most cases were idiopathic (92.5%), with a predominance of males. The mean cast was 6 (2-20). Twenty patients (50%) underwent a new tenotomy of the Achilles, and 12 patients (30%) older than four years also underwent transposition of the anterior tibialis. The recurrence rate was 15% (6 patients), with two cases requiring major reinterventions (tarsectomy and first-ray elevation). Three cases evolved with deformities due to hypercorrection (one calcaneus-cava and two plane-valgus). The initial Pirani was 3.9, and the end was 0.5. According to the functional classification, 42.1% of the feet were considered “excellent”, 47.4% “good”, 8.77% “regular”, and 1.75% “poor”, totaling more than 89.5% of plantigrade feet. Conclusion: The Ponseti method has been shown to be a treatment choice for CCF previously submitted to posteromedial release. With a high functional success rate and potential to avoid further extensive surgeries.